Analisis Stres Kerja Karyawan pada PT Bank Rakyat Indonesia (Persero) Tbk Cabang Bogor - Rahmawati, Siti (Jurnal Manajemen, 2009)
Most organizations face the dynamic environment and change regularly. The increasing bank competition tightly brings current competition which is not anymore only at price competition, interest and statistics, but also non-price competition. This condition will increase work stress level of employees. The objective of this research is to identify work stressors and stress symptoms, analyze work stress level totality based on characteristic of employees and identify stress management according to employees perception and management perception of PT BRI (Persero) Tbk Bogor. The result shows that the work stressors consist of  duty demand, role demand, interpersonal demand, organization structure, organization leadership and organization life cycle.  The symptoms of stress consist of physiological, psychological and behavioral. Work stress level of PT BRI (Persero) Tbk Bogor employees totality be at low category.  All the characteristic of employees don’t have significant relationship with work stress. No significant work stress differences based on all the characteristic of employees. The management of PT BRI (Persero) Tbk Bogor has already striven stress management but hasn’t optimal in that implementation. Keyword: work stress, work stressors, stress symptoms and stress management.